Designing Wooden Lounge Chairs Using ZMET: From Deep Need Discovery to Value Hierarchy Construction - Yong Han; Wumin Ouyang; Hemin Du; Zebin Qiao; Daren Wei (BioResources)
Traditional furniture design methods often fall short in revealing users’ deeper psychological and emotional needs. This study innovatively introduced the Zaltman Metaphor Elicitation Technique (ZMET) as an exploratory tool in the field of furniture design to bridge the cognitive gap between latent user needs and practical design. Through image collection, laddering interviews, and Kelly Repertory Grid Technique (RGT), cognitive modeling was conducted with six high-involvement users. A total of 119 concepts were identified, covering ten design attributes (e.g., “ergonomic fit,” “warm color tones”), seven emotional needs (e.g., “stress relief,” “immersive experience”), and five value hierarchies (e.g., “sense of belonging,” “self-actualization”). The resulting Hierarchical Value Map (HVM) illustrated a three-level structure of “attribute–consequence–value,” clearly mapping the psychological pathway from product features to core user values. The findings revealed that users expect more than basic functionality from wooden lounge chairs, seeking emotional resonance, lifestyle alignment, and identity expression. ZMET was shown to be effective in uncovering non-verbalized user needs and offers a theoretical and methodological framework for value-driven, user-centered furniture design.